Microbiome Analyses Demonstrate Specific Communities Within Five Shark Species - Storo, Rachael; Easson, Cole; Shivji, Mahmood; Lopez, Jose V. (Frontiers in Microbiology, 2021)
Profiles of symbiotic microbial communities (“microbiomes”) can provide insight into the natural history and ecology of their hosts. Using high throughput DNA sequencing of the 16S rRNA V4 region, microbiomes of five shark species in South Florida (nurse, lemon, sandbar, Caribbean reef, and tiger) have been characterized for the first time. The microbiomes show species specific microbiome composition, distinct from surrounding seawater. Shark anatomical location (gills, teeth, skin, cloaca) affected the diversity of microbiomes. An in-depth analysis of teeth communities revealed species specific microbial communities. For example, the genus Haemophilus, explained 7.0% of the differences of the teeth microbiomes of lemon and Caribbean reef sharks. Lemon shark teeth communities (n = 11) contained a high abundance of both Vibrio (10.8 ± 26.0%) and Corynebacterium (1.6 ± 5.1%), genera that can include human pathogenic taxa. The Vibrio (2.8 ± 6.34%) and Kordia (3.1 ± 6.0%) genera and Salmonella enterica (2.6 ± 6.4%) were the most abundant members of nurse shark teeth microbial communities. The Vibrio genus was highly represented in the sandbar shark (54.0 ± 46.0%) and tiger shark (5.8 ± 12.3%) teeth microbiomes. The prevalence of genera containing potential human pathogens could be informative in shark bite treatment protocols and future research to confirm or deny human pathogenicity. We conclude that South Florida sharks host species specific microbiomes that are distinct from their surrounding environment and vary due to differences in microbial community composition among shark species and diversity and composition among anatomical locations. Additionally, when considering the confounding effects of both species and location, microbial community diversity and composition varies.